Wellbore Stability Analysis Due to Turbulent Flow in Coiled Tubing Drilling - Bayati, Massoud (Curtin University, 2019)
One of the challenges of drilling petroleum and mineral exploration wells is borehole instability caused by the eroding action of drilling fluid in the annulus, called borehole erosion. My research focuses on developing the BET-M experimental set-up, RCT-M set-up, and developing the resulting numerical modelling method. My research findings show the range of pressure drop, hydraulic shear stresses, erosion rates and types of susceptible geological formations that can be affected during coiled tubing drilling.